2007
DOI: 10.1353/jod.2007.0056
|View full text |Cite
|
Sign up to set email alerts
|

Communism’s Many Legacies in East-Central Europe

Abstract: By focusing on the informal legacies that still shape the democracies of Central and Eastern Europe, we can attain a nuanced understanding of the region's postcommunist countries. In Poland, confrontational maximalism helps to generate governmental instability and poor policy continuity, while in Hungary there is now a question mark hanging over the future of the bounded flexibility that once reliably helped to center democratic politics. In the Czech Republic, instrumentalist attitudes and partisan-ideologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Shortly after the fall of the Berlin Wall, George Schöpflin (1993) correctly predicted that post-communist legacies would haunt the region even after the democratic systems and rule of law were instituted. Indeed, those legacies have an impact on the success of radical right parties in Eastern Europe (Bustikova & Kitschelt, 2009) and countries in Central and Eastern Europe continue to experience informal legacies and to be divided between the 'winners' of the transition and reform processes and the losers (Seleny, 2007). In Poland, the right-wing populist party Law and Justice (Prawo i Sprawiedliwość-PiS) originated from the anti-communist Solidarity trade union, and it continues to fight the influence of the Communist era security apparatus in Polish society (Pankowski, 2010).…”
Section: Empirical Applicationsmentioning
confidence: 99%
“…Shortly after the fall of the Berlin Wall, George Schöpflin (1993) correctly predicted that post-communist legacies would haunt the region even after the democratic systems and rule of law were instituted. Indeed, those legacies have an impact on the success of radical right parties in Eastern Europe (Bustikova & Kitschelt, 2009) and countries in Central and Eastern Europe continue to experience informal legacies and to be divided between the 'winners' of the transition and reform processes and the losers (Seleny, 2007). In Poland, the right-wing populist party Law and Justice (Prawo i Sprawiedliwość-PiS) originated from the anti-communist Solidarity trade union, and it continues to fight the influence of the Communist era security apparatus in Polish society (Pankowski, 2010).…”
Section: Empirical Applicationsmentioning
confidence: 99%
“…These stateowned firms were sponsored and controlled by the government-rendering them inert with respect to market dynamics (Li & Tang, 2010). State-owned firms in these economies were isolated from the world capitalist economy, and they had extensive linkages with the Soviet industry and long-standing ties with the barter-trading system of the Council for Mutual Economic Assistance (Bartlett & Seleny, 1998;Seleny, 2007). The transition shifted these economies toward private ownership, whether they were foreign or domestic by nature.…”
Section: Moderating Effect Of Firm Ownershipmentioning
confidence: 99%
“…According to Meyer and Peng (2015), repeated adaptation to changing environments has become a new normal in emerging economies. For instance, foreign firms, mainly western multinational companies, faced very different circumstances in the transition economies of Eastern Europe than in other capitalimporting regions during the earlier phases of foreign direct investment (Seleny, 2007). Thus, foreign firms had to learn, and particularly understand, local environmental business conditions (Meyer & Peng, 2015).…”
Section: Moderating Effect Of Firm Ownershipmentioning
confidence: 99%
“…5 Moreover, these authors found that the "boundary separating the authoritarian past from the liberalized present is a very porous one in eastern europe." 6 accordingly, scholars in this tradition have weighed in on the explanatory leverage of historical legacies (such as bureaucratic capacity 7 or informal regimes 8 ) compared to and combined with the dynamics of transitional politics in accounting for transition outcomes (such as democratization, 9 political party development, 10 or financial institutions 11 ). These authors have also assessed the relative importance of and interactions among various proximate and distant historical legacies-from the imprint of several decades of communism to the pre-communist socio-economic and political development of the countries in this region.…”
Section: Intra-region Diffusion As Bridging Temporal and Spatial Dependencementioning
confidence: 99%